The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/0102-33062016abb0198
|View full text |Cite
|
Sign up to set email alerts
|

Does fire determine distinct floristic composition of two Cerrado savanna communities on different substrates?

Abstract: We surveyed two savanna sites, one on fl at terrain with deep soil (DS), and the other on hilly terrain with rocky outcrops and shallow soil (RS), before and after an accidental fi re. We found that the fi re did not cause any signifi cant changes in the species composition or diversity of either community, and did not result in fl oristic homogenization. However, we did record a reduction in the density of plants and in basal area in the DS savanna in comparison with the RS savanna, as well as a higher rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
(54 reference statements)
0
12
0
2
Order By: Relevance
“…Nevertheless, despite those increments, there is no evidence that fire changes one phyto-physiognomy into another entirely, since edaphic limitations play an important role in determining Cerrado physiognomies [ 142 ]. Only when the vegetation before fires was already a more closed physiognomy can the increment of woody plants and tree species, after a long time of fire suppression (over 20 years), change phyto-physiognomies [ 143 , 144 , 145 ].…”
Section: Fire As An Ecological and Anthropological Factor In The Cmentioning
confidence: 99%
“…Nevertheless, despite those increments, there is no evidence that fire changes one phyto-physiognomy into another entirely, since edaphic limitations play an important role in determining Cerrado physiognomies [ 142 ]. Only when the vegetation before fires was already a more closed physiognomy can the increment of woody plants and tree species, after a long time of fire suppression (over 20 years), change phyto-physiognomies [ 143 , 144 , 145 ].…”
Section: Fire As An Ecological and Anthropological Factor In The Cmentioning
confidence: 99%
“…The rupestrian cerrado island encompasses only 8000 m 2 , and thus no more than 10 plots were set to assure sampling independence since both sampling areas were contiguous. Despite the fact that fire is a strong environmental filter in rupestrian environments (Figueira et al 2016), some studies have reported no floristic differences after fires (Lenza et al 2017), and so we disregard the effect of fire on the mosaic formation since no fires had been recorded for at least ten years in the study area.…”
Section: Study Area and Habitat Characterizationmentioning
confidence: 99%
“…We assume as a premise that the distribution pattern of the Cerrado sensu stricto shrub‐tree species is strongly associated with edaphic characteristics (Furley & Ratter, 1988; Lehmann et al, 2014; Oliveira‐Filho & Ratter, 2002; Reatto et al, 2008), as in the rupestrian environment, the physical–chemical conditions of soils are restrictive (Almeida et al, 2018; Benites et al, 2007; Fernandes et al, 2018, 2020; Moura et al, 2011; Negreiros et al, 2014; Oliveira et al, 2015; Schaefer et al, 2016). However, wildfires (depending on the frequency and intensity of fires) can modify the floristic composition and vegetation structure in the Cerrado sensu stricto (Coutinho, 1982; Gomes et al, 2016; Gomes et al, 2020; Henriques & Hay, 2002; Lenza et al, 2017; Miranda & Sato, 2005; Ribeiro et al, 2012), although the fire intensity is lower in the Rupestrian Savanna (Gomes et al, 2016; Kolbek & Alves, 2008; Lenza et al, 2017). Thus, our hypothesis is that the relief and limiting soil conditions in the Rupestrian Savanna have an influence at the intraspecific level, as a negative effect on the horizontal and vertical structure of the populations, as well as on the contribution of the species to the phytosociological structure of the community.…”
Section: Introductionmentioning
confidence: 99%